Physical Activity Level amongst University Students and Lecturers across Majors and Programs in Indonesia - Hariyanto, Agus; Mustar, Yetty Septiani; Sholikhah, Anindya Mar’atus; Rusdiawan, Afif; Susanto, Indra Himawan; Purnomo, Mochammad (Physical Education Theory and Methodology, 2023)
Background. Physical inactivity is the fourth leading risk factor contributing to the rapid increase in global mortality. The number is increasing in all sectors, with higher education institutions no exception. As university lecturers and students’ issues related to health and well-being are becoming more prevalent, the need to engage more time in doing physical activity becomes more important. The purpose of this study is to estimate the current physical activity level of students and lecturers across faculties and majors. Materials and methods. A cross-sectional study was conducted among 2698 students and 355 lecturers in November 2021. They completed an online Global Physical Activity Questionnaire (GPAQ) and reported the number of days and duration of activities they spent on studying or working, travelling, and recreational activities. All responses as to the duration were converted from hours into METs. Statistical analysis and data entry was performed using SPSS version 21. Results. A significant difference was found in METs scores between lecturers and students in three majors: Economics, Sports Science, and Science Education (p < 0.05). Other findings showed that the PA level among students and lecturers was found in the moderate category, although the low level of physical activity was also higher. Lack of physical activity is a major risk factor for non-communicable diseases and has a negative effect on the quality of life and mental health. Conclusions. Therefore, the university needs to carefully design policies and strategies to promote and enhance the physical activity and well-being of students, lecturers, staff, and all people involved.